Analisis Yuridis Pertangggungjawaban Pidana Dalam Hal Pemberitaan Hoax Oleh Media Online (Studi Putusan No. 1555/PID.Sus/2016/PN.Mdn) - Bambang Bambang (Fakultas Hukum universitas Islam Sumatera Utara, 2020)
Abstract Agreement is the source of the engagement in addition to other sources, namely law. This can be seen from Article 1233 of the Civil Code which states that: